Architecture as Irony in Michael Ondaatje's Novel In the Skin of a Lion - Viitamäki, Tuija Helena (My University, 2003)
In this study I have analysed the different, often ironic, ways of representing well-known works of architecture in Michael Ondaatje’s novel In the Skin of a Lion (1987). The Bloor Street Viaduct and the waterworks, which are under construction in the narrative, are famous landmarks in the city of Toronto. I have studied how the different characters (from different social classes) refer to the works of architecture in the novel, what kind of language they use, and what are their attitudes towards the artefacts. According to Michel Foucault, architecture may be used as a disciplinary tool in society. Buildings can support the prevailing hierarchical structures both symbolically and practically. On the other hand, Linda Hutcheon states that the ironic interpretation contests single meanings. In this study, I have claimed that the ironic interpretation of the works of architecture enables the characters to cross the imaginary boundaries in society, that is, irony as a literary device in the novel offers a view to Canadian society as manifold and dynamic. The conclusions of the study was that even though the edifices in the novel seem to function as a support of the disciplinary society, irony generates border-crossings, which mock the power hierarchies and gradually change the structures of society. Ironic representation in the novel, therefore, contests the notion of Canadian society as stagnant.
Keywords: disciplinary power; surveillance; irony; imaginary borders; subjectivity; colonial power; mimicry; orientalism; defamiliarization; carnivalesque; fi=Englannin kieli|en=English language|